Genetic studies to determine the risk of non-ischemic sudden death: review article: Estudios genéticos para determinar el riesgo de muerte súbita no isquémica: artículo de revisión - Castro-Mujica, María del Carmen (2022)
Heart disease is the cause of sudden death in more than 80% of cases. Ischemic heart disease is the cause for 90% of all sudden cardiac deaths, while in the remaining 10% of cases, heart diseases have a hereditary origin and comprise a wide spectrum of disorders that include cardiomyopathies and channelopathies. The aim of this review is to highlight the importance of genetic counseling for patients with hereditary cardiovascular disease and its evaluation by a multidisciplinary team.